OP0044 After how long of disease duration does the increased mortality risk appear in recent onset rheumatoid arthritis?. (12th June 2018) - Widdifield, J.; Bernatsky, S.; Huang, A.; Sayre, E.C.; Paterson, M.; Lacaille, D.
Abstract : Background: For decades studies showed that rheumatoid arthritis (RA) patients died earlier than their general population counterparts. Some inception cohorts have failed to detect an increased mortality risk, possibly due to limited followup or to improvement in mortality risk in cohorts of more recent onset. Objectives: To evaluate the risk of all-cause mortality in incident RA patients and to estimate when the increased risk appears amongst two Canadian inception cohorts with RA onset after 2000 Methods: Using a common protocol, we conducted 2 independent population-based cohort studies, using administrative health data, of incident RA patients in British Columbia (BC) and Ontario (ON), Canada over 2000 to 2015. In each province, we identified all RA patients (using validated criteria) diagnosed between 2000 and 2005 (to allow a minimum of 10 years of follow-up), and identified non-RA general population comparators for each RA patient, matched 1:2 on age, sex and index years. All patients were followed from index date until death (ascertained from vital statistics), out-migration, or end of study period (2015). Adjusted hazard ratios (HRs) and 95% CIs were estimated using multivariable Cox regression, controlling for baseline comorbidities, healthcare use, and socio-demographic factors. To estimate when the increased mortality risk appeared in incident RA patients, and to assess the proportional hazards assumption, we included an interaction between RA diagnosis and follow-up time in the multivariable model, to detect if and how the HR varied according to RA duration. Quadratic and logyear interactions were tested in the multivariable Cox models to assess linearity of the interaction. Results: Among 13 834 incident RA patients in BC (27 668 matched comparators), 66% were female with a mean (SD) age of 58 16 years at cohort entry. Among 27 405 incident RA patients in ON (54 810 matched comparators), 70% were female with a mean (SD) age of 56 16 years. The prevalence of individual comorbidities at baseline was comparable across RA cohorts. During follow-up, 3139 (23%) of BC RA patients and 6270 (23%) ON RA patients died, with corresponding crude mortality rates of 2.3 deaths per 100 person-years in both provinces. Crude mortality rate ratios for BC and ON were 1.11 (95% CI: 1.07 to 1.16) and 1.27 (95% CI: 1.23 to 1.31), respectively. Multivariable analyses detected an increased risk of all-cause mortality in incident RA (relative to non-RA) patients by 6 years of follow-up, with a linear relationship suggesting further increase over time (figure 1). By 10 years of followup, the adjusted HR for RA was 1.14 (95% CI: 1.07 to 1.22) in BC and.1.13 (95% CI: 1.08 to 1.18) in ON. Conclusions: In 2 large Canadian RA population-based inception cohorts, a small increased mortality risk appeared after 6 years of RA duration and increased to a 14% (in BC) and 13% (in ON) increased risk after 10 years. While these findings represent an improvement in the mortality risk associated with RA compared to previous reports in older historical cohorts, the increasing mortality risk associated throughout the disease course suggests increased efforts to prevent disease progression and optimise comorbidity management are needed. Disclosure of Interest: None declared